Visible-light-photocatalysis driven denitrogenative/radical 1, 3-shift of benzotriazole: access to 3-aryl-aminoquinoxalin-2(1H)-one scaffolds. Issue 2 (15th December 2022) - Yi, Bing; Tang, Huan; Yi, Ziqi; Gong, Huiling; Li, Daiguang; Zhang, Wenhui; Chen, Yizheng; Tan, Jian-Ping; Xie, Yanjun
Abstract : We described a visible-light-photocatalysis driven denitrogenative/radical 1, 3-shift of benzotriazole to generate unusual aromatic amine radical which then undergo direct amination with quinoxalin-2(1 H )-ones leading to 3-aryl-aminoquinoxalin-2(1 H )-ones. Abstract : The visible-light-photocatalysis driven denitrogenative/radical 1, 3-shift of benzotriazole to generate an unusual aromatic amine radical and then construct diverse 3-aryl-aminoquinoxalin-2(1 H )-ones bearing great synthetic values is disclosed. This photocatalytic reaction allows the direct formation of 3-aryl-aminoquinoxalin-2(1 H )-ones with highly tolerant functional groups. Furthermore, preliminary mechanistic investigations indicated that the reaction was induced by visible light and underwent the radical pathway. Insights gained from our studies are expected to advance general efforts to provide a green, economical and concise strategy to access 3-aryl-aminoquinoxalin-2(1 H )-ones, and also offer new opportunities towards obtaining arylamine radical and aromatic amine sources.